Longitudinal association of magnetic resonance elastography‐associated liver stiffness with complications and mortality. Issue 3 (19th December 2021) - Higuchi, Mayu; Tamaki, Nobuharu; Kurosaki, Masayuki; Inada, Kento; Kirino, Sakura; Yamashita, Koji; Hayakawa, Yuka; Osawa, Leona; Takaura, Kenta; Maeyashiki, Chiaki; Kaneko, Shun; Yasui, Yutaka; et al.
Summary: Background: Magnetic resonance elastography (MRE) has the highest diagnostic accuracy for liver fibrosis; however, the association between MRE‐associated liver stiffness and the development of hepatic and extrahepatic complications as well as mortality remains unclear. Aim: In this study, we investigated the longitudinal association between MRE‐associated liver stiffness and complications and mortality. Methods: This retrospective study included 2373 consecutive patients with chronic liver disease. All patients received standard of care and the development of complications was assessed every 1‐6 months. Results: Newly diagnosed hepatocellular carcinoma (HCC), decompensation, major adverse cardiovascular events (MACE), extrahepatic cancer and death were observed in 99, 117, 73, 77 and 170 patients respectively. In multivariable analysis, the adjusted hazard ratios (aHR) (95% confidence interval [CI]) for HCC, decompensation, MACE, extrahepatic cancer and mortality were 1.28 (1.2‐1.4), 1.34 (1.3‐1.4), 0.96 (0.9‐1.1), 1.00 (0.9‐1.1) and 1.17 (1.1‐1.2), respectively, with each 1‐kPa increase in liver stiffness. Similarly, the aHR (95% CI) for HCC, decompensation, MACE, extrahepatic cancer and mortality were 4.20 (2.2‐8.2), 67.5 (9.2‐492), 0.83 (0.4‐1.7), 0.90 (0.5‐1.7) and 2.90 (1.6‐5.4), respectively, in patients with cirrhosis (>4.7 kPa) compared to those with minimal fibrosis (<3 kPa). Conclusions: Increased MRE‐associated liver stiffness was associated with increased risk for HCC, decompensation and mortality in a dose‐dependent fashion but not with MACE or extrahepatic cancer, implicating a significant role for MRE in liver‐related events and mortality; however, further studies are warranted to explore its role in MACE and extrahepatic cancer. Abstract : In the study including 2373 patients with chronic liver disease who measured MRE, increased MRE‐associated liver stiffness was associated with increased risk for HCC, decompensation, and mortality in a dose‐dependent fashion but not with major adverse cardiovascular events (MACE) or extrahepatic cancer, implicating a significant role for MRE in liver‐related events and mortality; however, further studies are warranted to explore its role in MACE and extrahepatic cancer.